2019
DOI: 10.1111/cid.12722
|View full text |Cite
|
Sign up to set email alerts
|

Immediate placement of tapered implants with a moderately rough anodized surface and smooth collar in fresh extraction sockets: A retrospective analysis with 10‐year follow‐up

Abstract: Background There is limited long‐term data on hard‐ and soft‐tissue outcomes of implants immediately placed in postextraction sockets with immediate or early loading. Purpose To evaluate the clinical outcomes of immediately placed anodized tapered implants in consecutive patients with at least 10 years of follow up. Materials and Methods This retrospective analysis evaluated outcomes of 61 consecutive patients who received 89 tapered implants with an anodized implant body and machined collar. Implants were pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…TiUnite implants showed greater first-year crestal bone loss than the other modern implants but reached a relatively steady state without further notable bone loss on an annual basis. 44 45 In the present study, pronounced bone loss was also observed from 4 years to 7.5 years, and a stable mean bone level of 2 mm, which may be coordinated with biological width, was ultimately achieved. Further study is needed to discover the causes of these findings.…”
Section: Discussionsupporting
confidence: 66%
“…TiUnite implants showed greater first-year crestal bone loss than the other modern implants but reached a relatively steady state without further notable bone loss on an annual basis. 44 45 In the present study, pronounced bone loss was also observed from 4 years to 7.5 years, and a stable mean bone level of 2 mm, which may be coordinated with biological width, was ultimately achieved. Further study is needed to discover the causes of these findings.…”
Section: Discussionsupporting
confidence: 66%
“…It also compares favorably with the published literature. In the studies evaluating anodized implants with a follow‐up of more than 10 years, the mean marginal bone remodeling from implant insertion or prosthetic loading to last follow‐up ranged from −1.66 to −0.60 mm (Glauser, 2016; Mozzati et al, 2015; Mura, 2019), while in another study with bone loss assessed based on implant thread exposure, 90.4% of implants showed very low bone loss of less than 1 thread (Walton, 2016). A systematic review of radiological performance of implant‐supported single crowns estimated a mean bone loss of 1.3 mm after 10 years in function (Hjalmarsson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Glauser (2016) and Mozzati et al (2015) reported an 11-year and 12-year CSR of 97.1%, respectively; however, these studies were not limited to single-tooth restorations but also included partial and full arch restorations. In another study published by Mura (2019), using a tapered implant with an anodized body and a machined collar, a 10-year CSR of 100% was reported. These results suggest that anodized implants may offer a reliable solution for long-term clinical performance with survival rates better than those of machined surface implants.…”
Section: Outcome Measuresmentioning
confidence: 97%
See 1 more Smart Citation